Leptin-mediated proinflammatory bone marrow environment in acquired aplastic anemia. (April 2022) - Gao, Mengying; Ge, Meili; Huo, Jiali; Ren, Xiang; Li, Xingxin; Shao, Yingqi; Huang, Jinbo; Zhang, Jing; Wang, Min; Nie, Neng; Jin, Peng; Zheng, Yizhou
Highlights: Impaired AA-MSC differentiated toward adipocytes which secreted high amounts of leptin in AA-BM. The leptin interacted with leptin receptor to accelerate the T-cell responses in AA-BM. The leptin induced proinflammatory bone marrow environment by activating the JAK2/STAT3 pathway in AA. Abstract: Acquired aplastic anemia (AA), a paradigm of bone marrow failure syndrome, is mainly caused by abnormal immune activation. The enhanced adipogenesis of bone marrow-derived mesenchymal stem cell (BM-MSC) results in a fatty marrow of AA. Leptin, an adipokine mainly generated by adipocytes, has powerful proinflammatory effects on immune cells and is associated with various autoimmune diseases. However, the role of leptin in the hyperimmune status of AA remains unknown. In this study, we firstly discovered the higher leptin concentration in AA-BM than that in healthy donors (HD)-BM and myelodysplastic syndrome (MDS)-BM. Then, we found AA-MSC could express high amounts of leptin during the process of adipogenesis. Compared with HD, the leptin receptor was also highly expressed on T cells in AA-BM. Furthermore, leptin significantly accelerated the proliferation and activation of T cells in AA-BM. And, leptin promoted the production of interferon-γby T cells in AA-BM. However, leptin remarkably inhibited the conversion of CD4 + CD25 - T cells into CD4 + Foxp3 + T cells. Finally, we detected the cell signaling pathway in T cells from AA patients and found leptin could activate the STAT3 pathway. In summary, our data revealed the high expression of adipokine leptin in AA-BM which shaped a proinflammatory environment for T cells in AA-BM by activating the JAK2/STAT3 pathway.